Assessment of Haemodynamic Response to Nonselective Beta-Blockers in Portal Hypertension by Phase-Contrast Magnetic Resonance Angiography. (15th June 2017) - McDonald, Natasha; Lilburn, David M. L.; Lachlan, Neil J.; Macnaught, Gillian; Patel, Dilip; Jayaswal, Arjun N. A.; Hayes, Peter C.; Semple, Scott I.; Fallowfield, Jonathan A.
Abstract : A significant unmet need exists for accurate, reproducible, noninvasive diagnostic tools to assess and monitor portal hypertension (PHT). We report the first use of quantitative MRI markers for the haemodynamic assessment of nonselective beta-blockers (NSBB) in PHT. In a randomized parallel feasibility study in 22 adult patients with PHT and a clinical indication for NSBB, we acquired haemodynamic data at baseline and after 4 weeks of NSBB (propranolol or carvedilol) using phase-contrast MR angiography (PC-MRA) in selected intra-abdominal vessels. T1 mapping of liver and spleen was undertaken to assess changes in tissue composition. Target NSBB dose was achieved in 82%. There was a substantial reduction from baseline in mean average flow in the superior abdominal aorta after 4 weeks of NSBB therapy (4.49 ± 0.98 versus 3.82 ± 0.86  L/min, P = 0.03 ) but there were no statistically significant differences in flow in any other vessels, even in patients with >25% decrease in heart rate (47% of patients). Mean percentage change in liver and spleen T1 following NSBB was small and highly variable. In conclusion, PC-MRA was able to detect reduction in cardiac output by NSBB but did not detect significant changes in visceral blood flow or T1. This trial was registered with the ISRCTN registry (ISRCTN98001632 ).